Analysis of the Determinants of Financing Risk in Islamic Banks in Indonesia - Masfiatun Masfiatun; Nur Khayin Muhdlor; Mohammaad Zuhdi (Jurnal Indonesia Sosial Sains, 2024)
This research aims to analyze the factors affecting Islamic banks' financing risks. The data used in this study are from Sharia Commercial Banks nationally, with observations from 2018 to 2022 for a monthly time period, while the model in this study is multiple linear regression. The results of the study show that internal factors, such as ROA and CAR, have a significant negative effect on financing risk, while BOPO has a significant positive effect on financing risk. The conclusion of this study emphasizes the importance of bank performance in minimizing risks faced by banks, as well as the need to improve operational efficiency and human resource management.